Daily field checking list by Walter Rosene, May 13, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated May 13, 1936. This checklist was used by Walter Rosene to record birds sighted around North Bridge between 6:00 and 8:00, and Long Pond between 5:00 and 6:00. Plustek--flatbed